Bahasa Arab Sebagai Identitas Budaya Islam dan Pemersatu Keberagaman Suku - al Yamin, Daud Lintang (STAINI Press, 2023)
Arabic as a language that grows and develops in Arab countries, especially in the Middle East region. In essence, it is the language of religion and the language of unity for Muslims throughout the world. It was in this language that the Muslim holy book Al-Qur'an was revealed, and with it the Prophet Muhammad carried out his service to humanity. Because of this, in its development the Arabic language was named an international language by the United Nations on December 18, 1973 in recognition of its role and consistency as the language of culture and the unity of the people. The coronation is also a sign that Arabic is also actively used as a regular medium of communication in the association of nations at all levels. For this reason, Arabic cannot be separated from Islam, whose mission is power over the diversity of people. Aside from being a regulation of life, it is also a guideline for modern civilization. This can be seen vertically where the worship of a Muslim will not be valid if it is spoken in other than Arabic. And horizontally, Arabic is a language that has a diction of noble meaning and glorifies one another. Therefore, as long as this language is the obligatory language of a Muslim, then its role is unquestionable as a unifying language and strengthening brotherhood between individuals and groups.